REPRESENTASI CAPRES BONEKA DALAM MEME CAPRES BONEKA DI SOSIAL MEDIA - Dini Safitri (SEMIOTIKA: Jurnal Komunikasi, 2015)
This study aims to describe the meaning of representation in the meme presidential candidate stuffed doll in social media. Political year 2014 was a year full of political "war" symbol in social media. Among the "war", which later became tranding topic is "Candidates Dolls". At first, the symbol candidate dolls, starting from Prabowo statement. In the statement, Prabowo did not mention the name of a person who is declared as a "puppet candidate". Based on the situation of "war", the revelation leads to Joko Widodo, familiarly called Jokowi. However, the political situation has always had a new discourse, amid attacks signs and symbols, also circulated photos of Abu Rizal Bakrie (ARB) was hugging a doll, with its own narrative code. Then came Meme Trending Sosmed, "Come Guess Who Candidates Dolls Yes?", Which contains photos Surya Paloh, Roma Irama, Hatta Rajasa, Megawati, ARB, Wiranto, Prabowo, Susilo Bambang Yudhoyono (SBY), Jusuf Kala (JK) and Jokowi. The results showed there were 5 in the meme candidate Code dolls, ie hermeneutic code, the code semantic, symbolic codes, codes of narrative, and cultural codes. In the hermeneutic code contained puzzles candidate whose real doll? Semantic code shows signs of femininity, that no candidate who expressly acknowledges doll. Codes are symbolic antithesis of each point is, figures and figure hugging laughing doll. Code narrative explains that meme candidate doll is a story, have a groove and figures with various character. Code cultures showed the presence of myths about presidential politics doll in the year 2014. Keywords: Representation, Five Codes Barthes, Meme Candidates Dolls